1993
DOI: 10.1002/jlb.53.4.420
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids increase neutrophil adherence and integrin receptor expression

Abstract: Fish oils are abundant in polyunsaturated fatty acids of the n-3 series (in particular eicosapentaenoic, 20:5 and docosahexaenoic acid, 22:6). Such fatty acids are generally considered to be beneficial in the prevention of cardiac disease and to have anti-inflammatory properties. Neutrophil adherence is an essential early event in an acute inflammatory response, and we have demonstrated that both 20:5 and 22:6 stimulate adherence in vitro. Arachidonic acid (20:4, n-6) was also stimulatory. Significant simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…One way in which AA is able to promote the adherence of neutrophils is via the upregulation of surface receptor expression. Thus, not surprisingly, AA enhances the expression of the β2 integrin CD11b/CD18 on the surface of neutrophils [11,33]. This effect could be observed over an AA concentration range of 5-80 µM [11].…”
Section: Aa and Neutrophil Anti−microbial Activitymentioning
confidence: 70%
“…One way in which AA is able to promote the adherence of neutrophils is via the upregulation of surface receptor expression. Thus, not surprisingly, AA enhances the expression of the β2 integrin CD11b/CD18 on the surface of neutrophils [11,33]. This effect could be observed over an AA concentration range of 5-80 µM [11].…”
Section: Aa and Neutrophil Anti−microbial Activitymentioning
confidence: 70%
“…A number of studies have demonstrated that AA has a major influence on leukocyte responses. AA stimulates the production of oxygen radicals (12, [22][23][24][25][26], release of granule enzymes, increases adherence and damage to the endothelium (26)(27)(28), and inhibits cell migration (13).…”
Section: Discussionmentioning
confidence: 99%
“…Arachidonic acid has been shown to stimulate the neutrophil respiratory burst (1-3), degranulation (4,5), adhesion, and CD11b/CD18 expression (6) and prime neutrophils for increased responses to f-met-leu-phe and PMA (7). In addition, arachidonic acid stimulates the macrophage respiratory burst (8).…”
Section: Introductionmentioning
confidence: 99%